1998
DOI: 10.1038/sj.bmt.1701516
|View full text |Cite
|
Sign up to set email alerts
|

Disappearance of lupus anticoagulant after allogeneic bone marrow transplantation

Abstract: Summary:Lupus anticoagulant antibodies have never been reported to disappear after either allogeneic or autologous bone marrow transplantation in humans. We report the first case of disappearance of lupus anticoagulant antibodies in a patient without systemic lupus erythematosus or clinical evidence of other autoimmune disorders, who received an allogeneic bone marrow transplant as treatment for chronic myeloid leukemia. Although marrow transplantation is not a recognized therapy for antiphospholipid syndrome,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…15 Disappearance of the lupus anticoagulant has also been reported in a chronic myeloid leukemia patient who received allogeneic HSCT. 16 However, this is the first case to show decreased aCL titers and improved clinical symptoms of APS after autologous HSCT. The present case suggests the efficacy of autologous HSCT for patients with refractory APS.…”
Section: Discussionmentioning
confidence: 99%
“…15 Disappearance of the lupus anticoagulant has also been reported in a chronic myeloid leukemia patient who received allogeneic HSCT. 16 However, this is the first case to show decreased aCL titers and improved clinical symptoms of APS after autologous HSCT. The present case suggests the efficacy of autologous HSCT for patients with refractory APS.…”
Section: Discussionmentioning
confidence: 99%
“…Early animal models showed the effectiveness of SCT in APS. 3 This observation was not translated to clinical practice until the end of the 1990s when Olalla et al 22 reported the first case of disappearance of LA Abs in a patient without SLE treated with allogeneic SCT for chronic myeloid leukemia. Most reported studies described SCT for APS secondary to SLE.…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%
“…Also, disappearance of a lupus anticoagulant following allogeneic BMT in a patient with no clinical evidence of SLE has been described in the medical literature. 9 Rauch et al, 10 described that immunization of mice with phosphatidylethanolamine (PE) in the hexagonal II phase, but not the bilayer phase, resulted in the induction of anti-phospholipid antibodies. 10 Similarly, hexagonal (II) PE is specifically recognized by lupus anticoagulant antibodies in SLE patients and may play a role in the etiology of the disease.…”
Section: Discussionmentioning
confidence: 99%